Censored and multi-trait Bayesian models for genetic evaluation of milk, weight and reproductive traits in Guzerá cattle in tropical conditions - Brito, Lais Costa (2016)
We aimed to estimate genetic parameters for 305-d milk yield (MY305), growth (weaning – WW, yearling – YW and long yearling weights - LYW) and reproductive (age at first calving - AFC) traits in Guzerá cattle by using Bayesian multi-trait models and compare methodologies for handling censored data of age at first calving by Bayesian models. Data were provided by Brazilian Association of Zebu Cattle (ABCZ) and Embrapa Dairy Cattle Research Unit in partnership with the Brazilian Center of Guzerá Genetic Improvement (CBMG 2 ). The pedigree file (120,599 animals) included animals with phenotypic records and their known ancestors. Censored records were defined as AFC records out of range of 740 and 1860 days. Data including 69,157 AFC records were analyzed using seven different methods: conventional linear method (LM), simulation method (SM), penalty method (PM), a bitrait threshold-linear model considering (TLcens) or not (TLmiss) any prior information about censored records; and piecewise Weibull proportional hazards methodology considering (PWPHcens) or not (PWPH) censored records. For survival analyses, deviance information criterion (DIC) values suggested 0 and 2 piecewise change points in the baseline function of PWPH and PWPHcens methods, respectively. The additive genetic variance components estimated from LM, PM and TLmiss were similar. Heritability estimates for AFC ranged from 0.19 (TLcens) to 0.28 (SM) in non-survival approaches, and 0.40 and 0.46 to PWPH and PWPHcens methods, respectively. In general, genetic breeding values correlations from different methods and the percentage of selected bulss in common indicated moderate reranking, ranging from -0.28 (SM x PWPH) to 0.99 (TLmiss and LM). Comparisons based on cross-validation analyses, indicated TLmiss as a suitable alternative for predicting breeding values for AFC in this Guzerá population. In second chapter, systematic effects included sex and age at calving. The additive genetic and contemporary group (herd, year and season of birth) were included as random effects. Additionally, maternal genetic and permanent effects were included as random effects for weaning weight trait. Heritability estimates were 0.29 (MY305), 0.42 (WW), 0.49 (YW), 0.56 (LYW) and 0.25 (AFC). Genetic correlations between weight measures were higher than 0.83 and 0.25 (MY305 x WW), 0.32 (MY305 x YW) and 0.36 (MY305 x LYW) for other traits. AFC trait was negatively genetically correlated with milk and weight measures. These results suggest that selection for milk yield do not jeopardize selection for beef and reproductive efficiency and AFC censored data could be included in genetic evaluation considering a threshold-linear model in Guzerá cattle.